Unions, competition and international trade in general equilibrium - Bastos, Paulo; Kreickemeier, Udo (Nottingham, 2008)
"We develop a two-country, multi-sector model of oligopoly in which unionised and non-unionised sectors interact in general equilibrium. The model is used to study the impact of trade liberalisation, deunionisation and firm entry on wages and on welfare."